ANALISIS POTENSI PEDAGANG TERHADAP HASIL USAHA (STUDI PADA PEDAGANG SEKTOR INFORMAL DI JALAN MR. SARTONO KELURAHAN NUSUKAN BANJARSARI KOTA SURAKARTA) - MRIHRAHAYU R. (Fakultas Ekonomi dan Bisnis UTP Surakarta, 2015)
To respond increasing complexity and dynamism of the needs of consumers, the company formed an alliance organization of sales with other sales organizations, it aim to building a more cooperative marketing system and maintain an ongoing relationship with consumers. The purpose of this study were (1) To find empirical evidence of the influence of intensity to the level of trust and communication with the cooperation that exists. (2) to find empirical evidence of the influence of commitment to cooperation that exists. (3) to find empirical evidence of the influence of trust with the cooperation and effectiveness of relationship marketing (3) to find empirical evidence of the influence of co-operation with the effectiveness of relationship marketing. The types of data used in this study is the primary data drawn from retailers Tbk PT Indofarma Global Medika in Central Java. Sample as many as 100 persons determined by the method of random sampling. The results of analysis using Structural Equation Modelling(SEM) technique has been found that there was a positive influence on the intensity of communication with the level of trust and cooperation, significant effect between the commitment to cooperation that exists; there is a reciprocal relationship between trust in co-operation; influence on the effectiveness of the relationship of trust variables marketing, and there was a positive influence between the variables of cooperation with the effectiveness of relationship marketing. .Given the factors that influence relationship marketing such as communication, commitment, trust and cooperation have significant impact both directly and indirectly towards relationship marketing, therefore, should the management of PT Indofarma Global Medika Tbk. maximize the influence of these factors. Some ways that may be made by the management; companies need to do better interactions with retailers, enhance intimacy and learn the appropriate service expectations of retailers, giving attention to the ongoing transaction, and give attention to the relationship that the transaction in the future.